First Case of (Imported) Babesiosis Diagnosed in Canada. (1998) - Kunimoto, Dennis; Krause, Kevin; Morrison, Doug
Abstract : This paper describes the first case of babesiosis diagnosed in Canada. This case highlights the need for clinicians to be aware of diseases that may be endemic elsewhere and the importance of a travel history in a patient's assessment.